Establish In-House: A Pre-treatment Method of Fat, Oil and Grease (FOG) in Kitchen Wastewater for Safe Disposal - Al-Gheethi, Adel (International Journal of Integrated Engineering, 2019)
The direct disposal of untreated kitchen wastewater generated from the commercial restaurant into the sewerage system lead to increase the sanitary sewer overflow (SSO). In contrast, the disposal into the environment is associated with many adverse effects on the ecosystems. The present study aimed to develop a Fat, Oil and Grease (FOG) trap as a primary treatment of raw kitchen wastewater based on the gravity separation principle. The optimization of the separation process was determined using response surface methodology (RSM) based on flow rate and peak time of kitchen wastewater. The results revealed that the optimization removal of FOG was 93.48% with 8.27 L/min of flow rate and on 10.27 am of time sampling. FOG concentrations have dropped from 766.67 mg/L to 50 mg/L. These findings indicated that the FOG Trap was a reliable and exhibited efficiency for FOG removal from the kitchen wastewater.